2021
DOI: 10.1128/iai.00703-20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics for Antimicrobial Peptide Discovery

Abstract: Although antimicrobial resistance is an increasingly significant public health concern, there have only been two new classes of antibiotics approved for human use since the 1960s. Understanding the mechanisms of action of antibiotics is critical for novel antibiotic discovery, though novel approaches are needed that do not exclusively rely on experiments. Molecular dynamics simulation is a computational tool that uses simple models of the atoms in a system to discover nanoscale insights into the dynamic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…While previous review papers have shown how MD simulation has helped elucidate the role the lipid membrane plays in substrate and thus drug selection for membrane proteins [28][29][30][31][32], drug membrane interactions [33][34][35][36][37][38][39][40][41], drug delivery [3,[42][43][44][45], antimicrobial peptides [46][47][48][49][50][51][52][53][54], and methodologies [28,[55][56][57][58][59][60], this is the first review paper, that we are aware of, focusing on the entirety of the use of MD simulation to incorporate the role played by interactions with lipid membranes in drug design. This can be seen, in turn, as a case study of the potential for MD simulation to expand the paradigm of drug design to all aspects of the broader biophysical environment within which drug action occurs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While previous review papers have shown how MD simulation has helped elucidate the role the lipid membrane plays in substrate and thus drug selection for membrane proteins [28][29][30][31][32], drug membrane interactions [33][34][35][36][37][38][39][40][41], drug delivery [3,[42][43][44][45], antimicrobial peptides [46][47][48][49][50][51][52][53][54], and methodologies [28,[55][56][57][58][59][60], this is the first review paper, that we are aware of, focusing on the entirety of the use of MD simulation to incorporate the role played by interactions with lipid membranes in drug design. This can be seen, in turn, as a case study of the potential for MD simulation to expand the paradigm of drug design to all aspects of the broader biophysical environment within which drug action occurs.…”
Section: Introductionmentioning
confidence: 95%
“…Surprisingly, the number of clinical studies of antimicrobial peptides is, as of yet, relatively low (only 76) and the majority of these have ended in failure [761]; so far, only seven peptides have been approved for clinical use by the FDA [762]. However, the literature concerning antimicrobial peptides is extensive; prior comprehensive reviews of various aspects of antimicrobial and anticancer peptides have been published , including reviews focused specifically on computational studies [46][47][48][49][50][51][52][53][54]; we provide only a brief overview of this topic. Table 4 includes all antimicrobial peptides discussed in this paragraph.…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…These findings imply that peptide-based antimicrobials may evade multiple drug resistance mechanisms [61]. As a result, they may be a more advantageous alternative to conventional antibiotics [62].…”
Section: Discussionmentioning
confidence: 98%
“…Antibacterial lipopeptides, in general, work by damaging the bacterial cell wall [34] and inhibiting the growth of bacterial resistance mechanisms [62]. Surfactin impairs the permeability of the cell membrane [69].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, AMPs can be used as rediscovered [37] immunological effectors, to damage specific bacteria and target lysis of the pathogenic surface. Recent reports include among advantages the lesser tendency [38] to generate resistance [39], a low propensity to develop toxicity [25], better control of infection by intracellular bacterial pathogens as opposed to antibiotic ineffectiveness [21], anti-biofilm effects [25,35,40], and activation of immune cells [41]. Interestingly the patterns of mobile genetic elements are entirely different between the antibiotic and antimicrobial peptide resistance genes [42].…”
Section: Renewing Antimicrobial Peptides Potentialmentioning
confidence: 99%